Therapeutical Measures to Control Airway Tolerance in Asthma and Lung Cancer - Andreev, Katerine; Graser, Anna; Majer, Anja; Mousset, Stephanie; Finotto, Susetta (Frontiers in Immunology, 2012)
Airway tolerance is a specialized immunological surveillance which is activated by the cells of the lung to deal with and distinguish between innocuous and pathogenic inhalants. However, this distinction does not always occur. Airway tolerance is necessary to avoid the development of allergic disorders, such as asthma, which is dominated by a pathological expansion of Th2 and Th17 cells in the airways. By contrast, tumor cells induce tolerogenic factors in their microenvironment to evade T-cell mediated anti-tumor-immune responses. This review updates current understandings on the effect of the cytokines TGF-β, IL-10, and IL-17A on the lung immune responses to antigen, and analyzes their involvement in allergic asthma and lung cancer. The aim of the review is to evaluate where therapeutic intervention may be feasible and where it might fail. The multifunctional role of these cytokines further complicates the decision on the timing and concentration for their use as therapeutical targets. In fact, TGF-β has suppressive activity in early tumorigenesis, but may become tumor-promoting in the later stages of the disease. This dual behavior is sometimes due to changes in the cellular target of TGF-β, and to the expansion of the induced (i)-Tregs. Similarly, IL-17A has been found to elicit pro- as well as anti-tumor properties. Thus, this pro-inflammatory cytokine induces the production of IL-6 which interferes with Treg development. Yet IL-17A could promote tumor growth in conjunction with IL-6-dependent activation of Stat3. Thus, understanding the mechanisms of airway tolerance could help to improve the therapy to both, allergic asthma and lung cancer. Hereby, asthma therapy aims to induce and maintain tolerance to inhaled allergens and therapy against lung cancer tries to inhibit the tolerogenic response surrounding the tumor.